The Pediatric Disaster Mental Health Intervention: Meeting the Primary Care Special Needs of Children in the Aftermath of Disasters. Issue Volume 34:Issue s1(2019) (May 2019) - Cooper, Arthur; Frogel, Michael; Foltin, George
Abstract : Introduction: Effects of a disaster on a community's mental health can persist after the physical effects of the event have passed. The pediatric population is often overrepresented in disasters and prone to serious mental health disorders based on their age and parental/community response. Pediatric primary healthcare providers require the psychosocial skills necessary to work in disaster zones and to care for children in disasters. Aim: Pediatric Disaster Mental Health Intervention (PDMHI) was initially developed in response to Superstorm Sandy's impact on children and their families in New York City. The objective was to develop training for primary care providers in pediatric disaster mental healthcare and to study its impact on the trainees. Methods: A faculty of experts in pediatric mental health, psychiatry, psychology, and disaster preparedness was convened to develop curriculum. The faculty developed a four-hour intervention to equip healthcare providers with the skills and knowledge necessary to care for pediatric patients with mental health problems stemming from a disaster via evaluation, triage, intervention, and referral. Results: Three PDMHI training sessions were held. A total of 67 providers were trained. Of these, there were 31 pediatricians, 18 nurses, 8 social workers, 4 psychologists, 2 psychiatrists, and 4 others. Pre- and post-tests measured knowledge before and impact 3 months post-intervention. 62.5% of responding primary care providers made changes to their practice. 92% felt better equipped to identify, treat, and refer patients. 81% would be willing to work in a disaster zone and felt prepared to treat patients with disaster mental health issues. Discussion: PDMHI covers psychosocial responses to disasters from normal to mental health disorders. Participants gained tools for managing pediatric mental health issues in primary care. Study data showed an increase in the participants perceived knowledge and skills about pediatric disaster mental health, and willingness to participate in future disasters.